(untitled) (Latakia University Journal -Basic Sciences Series, 2024)
A simple and rapid electrochemical sensor has been developed to determine the concentration of pyridoxine chloride (vitamin B6). This method is based on the ion-association complex of the pyridoxine hydrochloride with cobalt chloride as ion pair in paste carbon electrode, and paraffin oil as a plasticizer. The electrode shows a Nernstian response within a range of concentrations (1×10-6-1×10-2) mol/L within a temperature range of (20-40)0C and a pH range of pH(2-4). It gave a Nernstian slope of 56.206±2mv/decade, a response time of 45sec, and a detection limit of 1.79×10-6 mol/L. It was also shown by calculating selectivity coefficients using Matched potential method that the proposed electrode shows high selectivity for vitamin B6 in the presence of a number of interfering ions.. The concentration of vitamin B6 in some pharmaceutical preparations was determined using the proposed method, giving a recovery of 100.9% and 101.8%. Comparison was also made with a reference method, and it was noted that there was good agreement in the results between the two methods, Therefore, this selective electrode can be adopted as a potential method for determining vitamin B6. Keywords: pyridoxine hydrochloride, paste carbon electrode, pharmaceutical preparations.